Effective Adsorbents Based on Biomaterials for Removal of Methylene Blue Dye from Water - Sriram, P. Janaki; Pravalika, K. Venkata; Meghana, P. Karunasri; Ravindhranath, K. (Asian Journal of Chemistry, 2019)
Biomaterials prepared from barks of Ficus benghalensis, Tamarindus indica and Acasia nilotica indica are investigated as adsorbents for the removal of methylene blue dye from waste waters using batch methods of extraction. Various physico-chemical parameters are optimized for the maximum removal of the dye. The extractions are found to be pH sensitive. Substantial adsorption is noted at high pHs. With simulated waters, 100 % removal of the dye is observed at pH 8/10 and at other optimum conditions of extraction with all the adsorbents developed. The optimum time needed for the maximum extraction of the dye is found to be in the order: Ficus benghalensis (120 min) > Tamarindus indica (90 min) > Acasia nilotica indica (30 min). The adsorption capacities of Ficus benghalensis sorbent, Tamarindus indica sorbent and Acasia nilotica indica sorbent are 50.0 mg/g, 66.7 mg/g and 100 mg/g respectively. In case of the Acasia nilotica indica sorbent, even at low pHs, substantial removal of the dye is effected. Co-anions (five fold excess) are least interfered while cations like, Ca2+, Mg2+ and Cu2+ have interfered to some extent but in no case, % removal has not come down below 90 %. It is interesting to note that Fe2+ and Zn2+ have maintained the maximum extraction synergistically. The developed procedures were successfully applied to real water samples too.